Temperature and doping effects on the transport properties of SrIn2P2 Zintl compound - Guechi, N.; Bouhemadou, Abdelmadjid; Benaisti, I.; Bin-Omran, Saad; Khenata, Rabah; Al-Douri, Yarub (Elsevier, 2020)
In this paper, we present and discuss temperature and doping effects on the electrical and thermal transport properties of SrIn2P2 Zintl phase along the [100] and [001] crystallographic directions. The calculations were performed by using the full-potential linearized augmented plane wave method in conjunction with Boltzmann's transport theory and Bardeen-Shockley's deformation potential with the carrier relaxation time and effective mass approximations. We calculated the band effective masses inside two energy windows of 125 meV; one above the fundamental conduction band minimum (FCBM) and the second below the valence band maximum (VBM). The calculated band effective masses exhibit a noticeable anisotropy and demonstrate that the n-type SrIn2P2 transport properties are better than those of the p-type one over the considered charge-carrier concentration range at room-, intermediate- and high-temperature, due to the proximity of the secondary conduction band minimums to the FCBM (∼58 meV). The n-type SrIn2P2 has a considerable Seebeck coefficient (429 μV/K), an extremely low electrical resistivity (0.90 mΩcm), and a relatively small lattice thermal conductivity (1.12 Wm−1K−1), which yield a figure of merit ZT of 0.87 for an electron concentration of 3.0 × 1019 cm−3 at 900 K. These results make SrIn2P2 a hopeful n-type thermoelectric material if we can further reduce its lattice thermal conductivity. © 2019 Elsevier B.V.